Ultrafine particle exposure for bicycle commutes in rush and non-rush hour traffic: A repeated measures study in Copenhagen, Denmark. (1st February 2022) - Bergmann, M.L.; Andersen, Z.J.; Amini, H.; Khan, J.; Lim, Y.H.; Loft, S.; Mehta, A.; Westendorp, R.G.; Cole-Hunter, T.
Abstract: Ultrafine particles (UFP), harmful to human health, are emitted at high levels from motorized traffic. Bicycle commuting is increasingly encouraged to reduce traffic emissions and increase physical activity, but higher breathing rates increase inhaled UFP concentrations while in traffic. We assessed exposure to UFP while cycling along a fixed 8.5 km inner-city route in Copenhagen, on weekdays over six weeks (from September to October 2020), during morning and afternoon rush-hour, as well as morning non-rush-hour, traffic time periods starting from 07:45, 15:45, and 09:45 h, respectively. Continuous measurements were made (each second) of particle number concentration (PNC) and location. PNC levels were summarized and compared across time periods. We used generalized additive models to adjust for meteorological factors, weekdays and trends. A total of 61 laps were completed, during 28 days (∼20 per time period). Overall mean PNC was 18, 149 pt/cm 3 (range 256–999, 560 pt/cm 3 ) with no significant difference between morning rush-hour (18003 pt/cm 3 ), afternoon rush-hour (17560 pt/cm 3 ) and late morning commute (17560 pt/cm 3 ) [p = 0.85]. There was substantial spatial variation of UFP exposure along the route with highest PNC levels measured at traffic intersections (∼38, 000-42000 pt/cm 3 ), multiple lane roads (∼38, 000-40000 pt/cm 3 ) and construction sites (∼44, 000-51000 pt/cm 3 ), while lowest levels were measured at smaller streets, areas with open built environment (∼12, 000 pt/cm 3 ), as well as at a bus-only zone (∼15, 000 pt/cm 3 ). UFP exposure in inner-city Copenhagen did not differ substantially when bicycling in either rush-hour or non-rush-hour, or morning or afternoon, traffic time periods. UFP exposure varied substantially spatially, with highest concentrations around intersections, multiple lane roads, and construction sites. This suggests that exposure to UFP is not necessarily reduced by avoiding rush-hours, but by avoiding sources of pollution along the bicycling route. Graphical abstract: Image 1 Highlights: Ultrafine particle (UFP) levels did not differ between rush- and non-rush-hour. We found large spatial variation in UFP levels along the route. Highest levels were seen close to construction work, heavy traffic and intersections.